Penyuluhan Hukum tentang Kejahatan Bulliying kepada Anak - Budi Handayani; Roidatus Shofiyah; Atmari Atmari; Tuti Herningtyas; Haniyah Haniyah (Institut Nalanda, 2025)
Bullying against children is a form of violence that frequently occurs in schools and communities and can seriously affect children’s psychological, social, and emotional development. The lack of public understanding regarding the dangers of bullying often causes such behavior to be considered normal or merely a joke. In fact, bullying can cause trauma, reduce self-confidence, disrupt the learning process, and even affect children’s mental health in the long term. This community service activity aimed to increase public understanding of the forms of bullying, its impacts, and legal protection for child victims of bullying. The activity was conducted at Citra Harmoni Housing Complex, Sidoarjo, on December 11, 2023, using legal counseling methods through lectures, discussions, and interactive question-and-answer sessions. The materials presented included physical, verbal, social, and cyber bullying, as well as prevention and handling efforts based on child protection laws in Indonesia. The results of the activity showed that participants gained a better understanding of the dangers of bullying and the importance of creating a safe, comfortable, and child-friendly environment. In addition, the community was encouraged to play a more active role in preventing and reporting bullying incidents in their surroundings.